SYNTHESIZE OF YTTRIUM IMPRINTED POLYMERS (Y-IPS) FOR SEPARATION OF YTTRIUM ION - Citra Agita, Nadia
Yttrium (Y) is one of the rare earth element (REE) which is widely used in various modern industries such as electronic filters, lasers, superconductors and various medical applications. Several methods have been used to separate and increase the levels of rare earth element, including stratified deposition, ion exchange resin, Solid Phase Extraction (SPE) and solvent extraction. However, the solvent extraction technique has drawbacks such as long operational time and wasted extractant. The stratified deposition method has drawbacks, that is use of too much solvent, this ion exchange resin has the disadvantage of slow mass transfer rate, and the drawback of Solid Phase Extraction (SPE) has low selectivity. In this study, Yttrium ion separation process was developed using a way of synthesizing polymer functionalization materials, namely ion imprinted polymers (IIPs). This porous polymer material can bind and release an ion through the formation of monomer bonds with metal ion complexes and their ligands, where metal ions are released from the polymer matrix and form a metal ion mold. IIPs has advantages compared to other polymer-based adsorbents such as the use of a small amount of polymer substance, can be regenerated so it can be used repeatedly for the same analysis, and a high level of selectivity. In this study, ion imprinted polymers (IIPs) were synthesized with the complex Yttrium (III), 5,7-dichloroquinolin8-ol (DCQ), and 4- vinylpyridine (VP) (Y-DCQ-VP) and polymerized using methyl methacrylate (MMA) as monomer and ethylene glycol dimethylacrylate (EGDMA) as crosslinker and their characterization using FTIR. The optimum adsorption process of functional materials on Yttrium ion occurred at pH 6, and the contact time was 30 minutes. The results of the study of adsorption kinetics showed the adsorption process followed pseudo-second order kinetics. The results of the literature study indicate the yttrium ion adsorption process using ion-printed polymer material (Y-IPs) occurs at the optimum initial concentration in the range of 30-80 mg/L, the optimum mass of the adsorbent is in the range of 10-30 mg, selective for the mold metal, and predicted to follow the Langmuir isotherm model.